2008
DOI: 10.1128/jcm.02437-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clostridium difficile Strains Isolated from Patients in Ontario, Canada, from 2004 to 2006

Abstract: Clostridium difficile is the bacterium most commonly surmised to cause antimicrobial-and hospital-associated diarrhea in developed countries worldwide, and such infections are thought to be increasing in frequency and severity. A laboratory-based study was carried out to characterize C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 44 publications
(30 reference statements)
7
64
3
Order By: Relevance
“…Thus, like REA, some NAP strain designations appear to encompass more isolate types than are recognized by the other typing methods. Martin and colleagues have made this same observation (32). For a laboratory wishing to initiate typing of C. difficile isolates, the Simpson's index of diversity scores and Wallace coefficients from our data set indicate that PCR-ribotyping should be the primary method of strain differentiation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, like REA, some NAP strain designations appear to encompass more isolate types than are recognized by the other typing methods. Martin and colleagues have made this same observation (32). For a laboratory wishing to initiate typing of C. difficile isolates, the Simpson's index of diversity scores and Wallace coefficients from our data set indicate that PCR-ribotyping should be the primary method of strain differentiation.…”
Section: Discussionmentioning
confidence: 90%
“…Our data indicate that group DH strains could be ribotypes 002, 046, and 053 in addition to 106, while group J strains could be ribotype 046 in addition to ribotype 001, potentially altering the interpretation of the data. Martin and colleagues typed 1,080 C. difficile isolates from Ontario, Canada, by multiple methods, including PCR-ribotyping, but performed PFGE and toxinotyping only on selected isolates (32). While the study did not provide adequate information about the congruence of the typing methods, the authors did note that NAP1 isolates could be assigned one of three ribotypes and that NAP2 isolates could be divided into four distinct ribotypes.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, 12 C. difficile isolates with vancomycin MICs of 4 mg/liter, comprising PCR ribotypes 106 (n ϭ 6), 001 (n ϭ 5), and 027 (n ϭ 1), were observed (69), compared with only a single isolate in our prior study (9). In a similarly large susceptibility study of 1,080 stool samples from diagnostic laboratories in Ontario, Canada, Martin et al reported 19 (1.8%) C. difficile isolates with metronidazole MICs of Ͼ8 mg/liter and 4 isolates with vancomycin MICs of 4 mg/liter (128). However, the C. difficile isolates (including PCR ribotypes 027 and 078) were only transiently resistant by Etest, with resistance apparently being lost upon repeated subculturing, which reflects data from previously reported in vitro studies (151).…”
Section: Susceptibility Of C Difficile To Metronidazole and Vancomycinmentioning
confidence: 99%
“…Clostridium difficile infection (CDI) has increased in frequency and severity in North America and Europe over the last 5 years, largely due to the emergence of the epidemic PCR ribotype 027 strain (10,11). The diagnosis of CDI is usually based on a clinical history of recent antimicrobial usage and diarrhea in combination with laboratory tests (9).…”
mentioning
confidence: 99%